Air Cushion Storing Energy Promoting Droplets Retraction and Flow on Engineering Porous Bionic Lotus Surfaces. Issue 16 (20th April 2022) - Zhu, Zewei; Li, Jingbo; Luo, Yimin; Tan, Sheng; Wei, Manjun; Lai, Ziming; Luo, Zhuangzhu
Abstract: Porous bionic self‐cleaning surfaces with low contact time of droplets show good potentials in anti‐icing, drag reduction, antifouling, etc. However, the reason of asymmetric and fast retraction on inclined surfaces after droplet impact is not clear. Here, it is reported that the fast retraction is mainly ascribed to the "air cushion" in porous surface acting as "energy reservoir" that stores excess kinetic energy of droplet during spread and returns it back promoting droplets retraction with contact time 20–40% off. Besides, the pinning effect and wetting state transition result in the asymmetric morphology evolution and suddenly stretch along tangential. A physical model of droplet asymmetric retraction including the influence of dynamic wetting angle f DCA, pinning effect f Pin, and air cushion f Air is innovatively proposed to describe droplet morphologic evolution. The fundamental understanding of droplets impact dynamic on inclined surfaces is beneficial for engineering applications of extremely wettable surfaces. Abstract : Herein, the mechanism of air cushion storing energy resulting in droplet's asymmetric and fast retraction on engineering porous bionic lotus surfaces is revealed for the first time.